Validation of the Scottish Social Care Survey using data from Renfrewshire Council. - Henderson, David; Bailey, Nick; McCowan, Colin; Mercer, Stewart (International Journal of Population Data Science, 2018)
Background The Social Care Survey (SCS) is collected annually by the Scottish Government (SG) from all of Scotland’s 32 local authorities. In addition to other information, it details the amount of home care delivered to all individuals in receipt of this service during a specified census week. How well this census represents care delivered throughout the year is unknown. Objectives Using complete data from one local authority area: 1. Quantify the annual proportion of individuals receiving care during the census week. 2. Describe differences in type and duration of care packages received during/not during the census week. Methods A data sharing agreement was completed with Renfrewshire council to transfer all social care data for the years 2006-2016 to a safe haven environment. A time series was created identifying how much care each individual received at weekly intervals during the study period allowing comparison of counts of individuals at any given week with total counts for financial years. Differences in packages received during/not during the census week in each financial year were compared using the Mann-Whitney U test. Findings 41,002 packages of home care for 10,130 individuals over the age of 65 (64% female), were analysed. The proportion of people receiving care in the census week varied from 54.1% to 64.8% of the total number of individuals receiving care in a given financial year. Approximately half of packages received during the census week were of similar duration and intensity (weekly hours delivered) as packages not captured by the census. The remainder tended to be of much longer duration (>1 year) and less intensity. Conclusions The SCS represents approximately 60% of individuals receiving home care in the Renfrewshire council area and a representative sample of packages of care delivered.